Does the Kingdom Need a King? Anti-Monarchical Christology in the Canonical Gospels and the Historical Jesus - McMahon, Christopher (Irish theological quarterly, 2025)
The image of Christ the King often overlooks or sidelines a distinctively anti-monarchical Christological tradition in the gospels, one that is perhaps rooted in the historical message and practice of Jesus himself. This anti-monarchical tradition, ensconced as it is within the very familiar and normative royal and messianic Christology of the NT, invites contemporary believers to reconsider the image of Christ as “king.”